Checklist of the tick (Acari: Argasidae, Ixodidae) species of Pakistan - Ramzan, Muhammad; Naeem-Ullah, Unsar; Masood Bokhari, Syed Haroon; Saba, Shafia; Khan, Khalid Ali; Saeed, Shafqat (Veterinaria italiana, 2020)
In developed and underdeveloped countries, ticks are important vectors transmitting various pathogens that cause diseases of veterinary and public health importance, like babesiosis, theileriosis, Crimean‑Congo haemorrhagic fever (CCHF) and many more. Many species of ticks have been reported in scientific literature from Pakistan, which need to be listed for ready reference. For this purpose, a checklist of tick species recorded in Pakistan is presented here after comprehensive review of the available literature on the subject. Overall, nine genera and 53 species of ticks infesting animals in Pakistan are presented in this checklist.